The Influence of the Children Learning in Science (CLIS) Learning Model and Students' Learning Styles on Improving Students' Conceptual Understanding and Motivation to Learn Mathematics - Ayu Dewi Prastika Putri; Rizky Wahyu Yunian Putra; Siti Ulfa Nabila (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Children Learning in Science (CLIS) learning model emphasizes the process of reconstructing students' understanding by directing changes in initial misconceptions towards a more accurate scientific understanding. This study aims to: (1) analyze the influence of the CLIS learning model on improving conceptual understanding and mathematical learning motivation simultaneously; (2) analyze the influence of students' learning styles on improving conceptual understanding and mathematical learning motivation simultaneously; (3) analyze the influence of the CLIS learning model and students' learning styles simultaneously on improving conceptual understanding and mathematical learning motivation; (4) determine the influence of the CLIS learning model on improving conceptual understanding and mathematical learning motivation partially; (5) determine the influence of students' learning styles on improving conceptual understanding and mathematical learning motivation partially; and (6) determine the influence of the interaction between the CLIS learning model and students' learning styles on improving conceptual understanding and mathematical learning motivation partially. This study uses a quantitative approach with a quasi-experimental research type. The research population was all eighth grade students of SMP Negeri 2 Abung Semuli, North Lampung, with sample determination using cluster random sampling technique. The data collection instruments included a learning motivation questionnaire, a learning style questionnaire, and a mathematical concept comprehension ability test. The data obtained were analyzed using a MANOVA test with a significance level of 5%. The results of the study showed that: (1) the CLIS learning model had a significant effect on students' conceptual understanding and mathematical learning motivation, with the highest achievement in conceptual understanding; (2) learning styles had a significant effect on students' conceptual understanding and mathematical learning motivation, where in conceptual understanding the auditory learning style showed the best results compared to visual and kinesthetic learning styles, while in learning motivation the kinesthetic learning style obtained the highest results compared to visual and auditory learning styles; (3) the CLIS learning model and students' learning styles simultaneously had an effect on improving students' conceptual understanding and mathematical learning motivation; (4) the CLIS learning model partially had an effect on improving students' conceptual understanding and mathematical learning motivation; (5) learning styles partially had an effect on improving students' conceptual understanding and mathematical learning motivation; and (6) there is an influence of the CLIS learning model and students' learning styles on increasing conceptual understanding abilities, but there is no influence on mathematical learning motivation partially.